Copper Bead Therapy in Severe Bone Infection: A Rabbit Tibial Model - Surdu-Bob, Carmen C.; Vlase, Ene; Barbuceanu, Florica; Turcu, Danut; Coman, Mariana; Badulescu, Marius; Oporanu, Mariana; Coman, Cristin (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective We investigated the benefits of a local preventive therapy based on copper beads against severe bone infection using a rabbit open tibial fracture model.Materials and Methods Cotton mesh balls soaked in a very high concentration of Staphylococcus aureus ATCC 6538 culture were inoculated in drilled holes of the tibiae of treated and control groups. The treated group was also implanted with small copper beads simultaneously, as prevention therapy.Results Survival rate in the treated group was 67% compared with 25% in the control group (difference 40%, for a 95% confidence interval: 40%, 93.4%). The few remaining animals in the control group had bone lesions which developed into osteomyelitis, while the tibiae of treated group had clear signs of reparatory processes. Sixty days after inoculation, signs of local-only toxicity were observed in healthy tibia of a separate non-infected control group. Drawbacks of copper toxicity were weighed against the threat of septicaemia and also against prolonged use of powerful systemic antibiotic medications in severe bone contamination.Cinical Significance It was found that the proposed therapy prevented septicaemia and the spread of infection, and it also induced reparatory processes. The findings of this study may be relevant in antisepsis of open fractures in less appropriate medical settings (such as military camps or remote locations), as well as in severe bone infections.
Keywords: osteomyelitis; septicaemia; bone infection; rabbit; copper bead